The impact on the South African economy of alternative regulatory arrangements in the petroleum sector - Heinrich Bohlmann; Rod Crompton (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This paper adds quantitative analysis to the study by Crompton et al. (2020), in which various alternative regulatory arrangements regarding the petrol price in South Africa were explored. We use a multi-sector dynamic computable general equilibrium model for South Africa to conduct our economic impact analysis. Five scenarios are modelled, first individually to correctly calibrate the shocks, and then cumulatively to find the overall economy-wide effects of the proposed reforms. Under the most comprehensive set of reforms to the determination of petrol prices, which seeks to emulate market forces, the South African economy is seeing substantial benefits. GDP is expected to rise by 0.67 per cent and real wages by over 1.1 per cent relative to the baseline. Refineries are assumed to shrug off reforms targeted at removing pure profits earned via the import parity price (Basic Fuel Price) methodology by accepting a slightly lower rate of return, enabling them to meet the expected increase in demand for petrol on the back of the lower consumer prices achieved via the reforms. Whilst job losses at fuel service stations may be expected as a result of reduced revenues and margins, increased activity and job opportunities in the rest of the economy, facilitated through cheaper trade and transport margins, will more than offset those losses.
Keywords: C68; K23; L59; D40; 330; computable general equilibrium; economic impact; petrol price; South Africa